Nanobiocatalysts: Nanozymes and Nanobioconjugates in Heterogeneous Catalysis and Electrocatalysis - Silva, Rafael Trivella Pacheco da (2022)
The use of metallic nanoparticles for biocatalysis has been steadily increasing due to their great catalytic potential, stability against complex media and recyclability. In addition, nanocatalysis can be benefited by external stimuli such as localized surface plasmon resonance (LSPR), whose optical, electronic and thermal effects are capable of intensifying or even modifying the catalytic mechanisms of the original reactions. This thesis is dedicated to investigating: i) metallic nanoparticles that can act as enzymes, in the so-called nanozymes and ii) metallic nanoparticles as supports for the immobilization of proteins in nanobioconjugates. The materials were studied from the nanobiocatalytic point of view and under the action of LSPR stimulus. In the first series of materials, nanozymes, silver nanoparticles (AgNP) were studied as antimicrobial agents against multidrug-resistant P. aeruginosa. Under light stimulus on LSPR, AgNP are able to cause cell death to 100% of bacteria in just 1 h of treatment. This efficiency is related to the higher production of reactive oxygen species (ROS) in the combination of AgNP and light, demonstrating the effect of LSPR. Bimetallic AgAu nanoparticles were also studied. Bimetallic AgAu alloys supported on SiO2 were synthesized mechanochemically and used in the hydrogenation of 2-nitroaniline. In this case, a 4-fold increase in the rate constant was observed, as well as an increase in catalytic conversion compared to the individual metals. Bimetallic AgAu nanoshells supported on graphene oxide (GO) and SiO2 submicrospheres were synthesized by galvanic substitution in solution. The nanoshells were tested as peroxidases for the electrochemical detection of H2O2 by its reduction reaction (HPRR), with influence of the composition and support, as well as the excitation region of the LSPR. Compared to the dark, AgAu/GO showed a 100% increase in sensitivity under the stimuli of 405 or 533 nm, while AgAu/SiO2 led to a 120% improvement under the stimulus of 650 nm. In the second type of materials studied, nanobioconjugates, gold nanoparticles (AuNP) were studied as support for immobilization of two biomolecules: Lipase from Candida sp. (CALB) and Cytochrome C (CytC). Immobilized CALB showed improvement in its catalytic activity under LSPR stimulation of AuNP. The enzyme was investigated in terms of secondary structure changes by local heat generation. Circular dichroism and Raman showed intense changes, especially in the α-helix, after immobilization, but also under the change of temperature and incidence of light. Molecular Dynamics (MD) demonstrates that these stimuli can lead to the exposure of the Ser105- Asp187-His224 catalytic triad and, therefore, would promote greater catalytic activity. Similarly, when CytC is immobilized in AuNP, changes in its secondary structure were observed, especially with a significant loss of -helix and gain of β-sheets, in addition to a considerable improvement in thermal stability. Catalytically, the CytC@AuNP nanobioconjugate showed a 68% improvement in catalytic conversion. Under LSPR, only the nanobioconjugate had a performance improvement of 12%. Thus, this thesis demonstrates the advantages of using metallic nanoparticles in nanobiocatalysis, whether through the use of nanozymes or nanobioconjugates, also expanding what we know about the interaction of LSPR and biomolecules.